IMPROVEMENT OF COMMUNITY LEARNING OUTCOMES THROUGH LEARNING METHODS INQUIRY IN GRADE IV ELEMENTARY SCHOOL STUDENTS: IMPROVEMENT OF COMMUNITY LEARNING OUTCOMES THROUGH LEARNING METHODS INQUIRY IN GRADE IV ELEMENTARY SCHOOL STUDENTS - Musdiani Musdiani (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The purpose of this research is to determine whether the use of the inquiry method can enhance the activities of students and teachers in the PKn subject for fourth-grade students at Kuta Rentang Elementary School. Another objective is to find out whether question-based learning can improve the learning outcomes of PKn for fourth-grade students at Kuta Rentang Elementary School. The research results show that the average teacher activity was 2.7 in cycle I and 3.7 in cycle II, both of which fall into the very good category. The average student activity in cycle I was 2.37, and the average student activity in cycle II was 3.37, both of which also fall into the very good category. The research results show that the average teacher activity was 2.7 in cycle I and 3.7 in cycle II, both of which fall into the very good category. The average student activity in cycle I was 2.37, and the average student activity in cycle II was 3.37, both of which also fall into the very good category. The results of cycle II indicate that the average learning outcome of the 4th-grade students in PKn lessons is 76.25. This indicates that the students' skills are already above the determined KKM, which is 70. The number of students who have completed the task is 7 students with a percentage of 87.5%. Meanwhile, the number of students who have not completed the task is 1 student with a percentage of 12.5%. The highest score achieved by students in the second cycle stage is 90, and the lowest score is 45.